Methoxychlor induces oxidative stress and impairs early embryonic development in pigs - Geng, Zhaojun; Jin, Yongxun; Quan, Fushi; Huang, Siyi; Shi, Shuming; Hu, Bing; Chi, Zhichao; Kong, Ilkeun; Zhang, Mingjun; Yu, Xianfeng (Frontiers in Cell and Developmental Biology, 2023)
Introduction: Methoxychlor (MXC) is an organochlorine pesticide (OCP) that was formerly used worldwide as an insecticide against pests and mosquitoes. However, MXC is not biodegradable and has lipophilic characteristics; thus, it accumulates in organisms and affects reproductive function. MXC, as an estrogenic compound, promotes oxidative stress, induces oxidative stress damage to ovarian follicles, and causes miscarriages and stillbirths in females. In this research endeavor, our primary objective was to explore the ramifications of MXC regarding the developmental processes occurring during the initial stages of embryogenesis in pigs. Methods: In this study, we counted the blastocyst rate of early embryos cultured in vitro. We also examined the reactive oxygen species level, glutathione level, mitochondrial membrane potential, mitochondrial copy number and ATP level in four-cell stage embryos. Finally, apoptosis and DNA damage in blastocyst cells, as well as pluripotency-related and apoptosis-related genes in blastocyst cells were detected. The above experiments were used to evaluate the changes of MXC damage on early parthenogenetic embryo development. Results and Discussion: The results showed that early embryos exposed to MXC had a significantly lower cleavage rate, blastocyst rate, hatching rate, and total cell count compared with the control group. It was also of note that MXC not only increased the levels of reactive oxygen species (ROS), but also decreased the mitochondrial membrane potential (ΔΨm) and mitochondrial copy number during the development of early embryos. In addition, after MXC treatment, blastocyst apoptosis and DNA damage were increased, decreased cell proliferation, and the expression of pluripotency-related genes SOX2, NANOG, and OCT4 was down-regulated, while the expression of apoptosis-related genes BAX/BCL-2 and Caspase9 was up-regulated. Our results clearly show that MXC can have deleterious effects on the developmental processes of early porcine embryos, establishing the toxicity of MXC to the reproductive system. In addition, the study of this toxic effect may lead to greater concern about pesticide residues in humans and the use of safer pesticides, thus potentially preventing physiological diseases caused by chemical exposure.